Defective T-Cell Apoptosis and T-Regulatory Cell Dysfunction in Rheumatoid Arthritis - Malemud, Charles J. (Cells, 2018)
Rheumatoid arthritis (RA) is a chronic, progressive, systemic autoimmune disease that mostly affects small and large synovial joints. At the molecular level, RA is characterized by a profoundly defective innate and adaptive immune response that results in a chronic state of inflammation. Two of the most significant alterations in T-lymphocyte (T-cell) dysfunction in RA is the perpetual activation of T-cells that result in an abnormal proliferation state which also stimulate the proliferation of fibroblasts within the joint synovial tissue. This event results in what we have termed “apoptosis resistance”, which we believe is the leading cause of aberrant cell survival in RA. Finding therapies that will induce apoptosis under these conditions is one of the current goals of drug discovery. Over the past several years, a number of T-cell subsets have been identified. One of these T-cell subsets are the T-regulatory (T(reg)) cells. Under normal conditions T(reg) cells dictate the state of immune tolerance. However, in RA, the function of T(reg) cells become compromised resulting in T(reg) cell dysfunction. It has now been shown that several of the drugs employed in the medical therapy of RA can partially restore T(reg) cell function, which has also been associated with amelioration of the clinical symptoms of RA.